Geotectonic model of the deep structure of the Zmeinogorsky ore district of Rudny Altai according to geological interpretation of geophysical survey complex - Alexey S. Egorov; Dmitry F. Kalinin; Darya D. Sekerina (Известия Томского политехнического университета: Инжиниринг георесурсов, 2024)
Relevance. The relevance of the research of deep structure of the Zmeinogorsky ore district is caused by the search for hidden and poorly manifested pyrite-polymetallic mineralization on the surface within the Rudny Altai minerogenic zone. This task is of particular prognostic interest due to the high searchability of the area on the surface and the prospects for detecting hidden mineralization at deeper horizons. Aim. Geotectonic modeling of structural and material inhomogeneities of the Earth's crust of the Zmeinogorsky ore district based on a comprehensive interpretation of geological and geophysical data with the identification of patterns of localization of hidden and poorly manifested pyrite-polymetallic mineralization on the surface. Objects. Regularities of localization of hidden and poorly manifested pyrite-polymetallic mineralization on the surface within the Zmeinogorsky ore district of the Rudny Altai. Methods. Processing of areal and profile materials of the study of the Rudny Altai, qualitative and quantitative interpretation of heterogeneous geological and geophysical information at the regional and detailed levels. The study of the history of development and geodynamic conditions of the formation of ore-bearing structures of the Zmeinogorsky ore district with the identification of geological and structural prognostic features at depths of practical interest. Results. Based on a comprehensive analysis of heterogeneous geological and geophysical data, the authors have carried out the historical-evolutionary and geodynamic interpretation of the mineragenic structures of the Zmeinogorsky ore district within the Rudny Altai; these materials can be used as the basis for regional forecast constructions using non-standard geological, structural and material (tectonic) signs; the special influence of tectonic events characterizing the situation of the active continental margin with complicating episodes of rifting was verified; the patterns of localization of pyrite-polymetallic ores in volcanogenic-sedimentary rocks were revealed with the justification of a set of predictive criteria.